Ambient aerosols increase stomatal transpiration and conductance of hydroponic sunflowers by extending the hydraulic system to the leaf surface - Burkhardt, Juergen; Zinsmeister, Daniel; Roth-Nebelsick, Anita; Hüging, Hubert; Pariyar, Shyam (Frontiers in Plant Science, 2023)
Many atmospheric aerosols are hygroscopic and play an important role in cloud formation. Similarly, aerosols become sites of micro-condensation when they deposit to the upper and lower surfaces of leaves. Particularly salts can trigger condensation considerably below atmospheric saturation, according to their hygroscopicity and the relative humidity within the leaf boundary layer. Salt induced water potential gradients and the resulting dynamics of concentrated salt solutions can be expected to affect plant water relations. Hydroponic sunflowers were grown in filtered (FA) and unfiltered, ambient air (AA). Sap flow was measured for 18 days and several indicators of incipient drought stress were studied. At 2 % difference in mean vapor pressure deficit (D), AA sunflowers had 49 % higher mean transpiration rates, lower osmotic potential, higher proline concentrations, and different tracer transport patterns in the leaf compared to FA sunflowers. Aerosols increased plant conductance particularly at low D. Probably thin films of salt solutions from deliquescent deposited aerosols enter into stomata and cause an extension of the hydraulic system. This hydraulic connection leads -parallel to stomatal water vapour transpiration -to wick-like stomatal loss of liquid water and to a higher impact of D on plant water loss. [J1] Due to ample water supply by hydroponic cultivation, AA plants thrived as well as FA plants, but under more challenging conditions, aerosol deposits may make plants more susceptible to drought stress. [J2]